1996
DOI: 10.1093/geronb/51b.2.p64
|View full text |Cite
|
Sign up to set email alerts
|

A Measurement Model of Cortisol Reactivity of Healthy Older Adults

Abstract: Research on the physiological adaptation process has found that stress is associated with the rate of cortisol secretion, the main hormone that reflects stress. However, considerable variation among subjects has been reported. Using a sample of older adults (N=46), we tested the hypothesis that cortisol reactivity is composed of (1) a situation-related component representing hypothalamic influence on cortisol secretion observed on three different occasions, and (2) a stable component representing a general tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Thirty minutes later, participants were invited to solve 70 addition problems from the SchaieThurstone Primary Mental Abilities Test (Schaie, 1985). Results from a previous study showed that this test was an acceptable stress activator in older adults (Pre´ville et al, 1996). The instructions were read to the participant and three examples were completed.…”
Section: Methodsmentioning
confidence: 99%
“…Thirty minutes later, participants were invited to solve 70 addition problems from the SchaieThurstone Primary Mental Abilities Test (Schaie, 1985). Results from a previous study showed that this test was an acceptable stress activator in older adults (Pre´ville et al, 1996). The instructions were read to the participant and three examples were completed.…”
Section: Methodsmentioning
confidence: 99%
“…Researchers in endocrinology and behavioral medicine indicated that salivary cortisol is as reliable as serum and urine assessments, and it can be readily obtained ). Studying older adults over a 9-month period, Preville et al (1996) reported a positive relationship between subjects' salivary cortisol levels and the stress induced in an experimental setting. In a study of current stress at six time intervals during 1 day, Smyth et al (1998) found that salivary cortisol increased with daily stressors and anticipated stress.…”
Section: Introductionmentioning
confidence: 97%
“…Cortisol has been shown to be a sensitive indicator of stressful situations in both younger and older populations (Preville et al, 1996;Smyth et al, 1998;Vedhara et al, 1999) and it has shown a small positive association with trait anxiety and depression (Van Eck, Berkhof, Nicholson, & Sulon, 1996). Researchers in endocrinology and behavioral medicine indicated that salivary cortisol is as reliable as serum and urine assessments, and it can be readily obtained ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have validated the direct radioimmunoassay of cortisol in saliva, determined the stability of salivary cortisol under various laboratory conditions, and documented correlations between levels of serum and salivary cortisol in various static and dynamic conditions (e.g., Kahn, Rubinow, Davis, Kling, & Post, 1988;Kirschbaum & Hellhammer, 1992Reid, Intrieri, Susman, & Beard, 1992). Those findings are often cited to justify the use of salivary cortisol in studies with children.…”
Section: Introductionmentioning
confidence: 99%